SYSTEMATIC REVIEW ON THE PSYCHOMETRIC, RELIABILITY AND VALIDITY PROPERTIES OF TRANSLATED NEUROPATHIC PAIN SCREENING TOOLS (DN4, LANSS AND PDQ) 1 JANUARY 2005 – 19 JULY 2019 - Fagbohun, T. R. (International Journal of Medicine and Medical Research, 2021)
Background. Different neuropathic pain screening tools (DN4, LANSS and PDQ) have been developed, translated into several local languages, and validated. To determine the reliability of these tools and their ability to differentiate between diagnosing neuropathic pain quality from nociceptive pain, a systematic review was conducted to synchronize properties and suggest the reliability of the translated version of these neuropathic pain-screening tools. Objective. To conduct an evidence-based systematic review to assess the psychometric, reliability and validity of the translated version of DN4, LANSS and PDQ between January 2005 and 2019. Methods. Two independent reviewers adopted the use of online (Internet) search machine (Pubmed, Scopus and Web of science) to search for the relevant articles based on JBI (Joanna Briggs Institute) inclusion criteria. Data extracted from the articles were synthesis in tabular form. Results. Twenty-six articles were included from DN4 (n=11), LANSS (n=8) and PDQ (n=4) translated from English language to eight local languages. The sensitivity and specificity of the DN4 studies ranged from 75% to 98% and 37.3% to 96%, respectively. The internal reliability (α) of the translated version of the DN4 ranged from 0.55-0.862. The sensitivity and specificity of the LANSS studies ranged from 75% to 98% and 37.3% to 96%, respectively. The internal reliability (α) of the translated version of the LANSS ranged 0.67-0.96. The sensitivity and specificity of the PDQ studies ranged from 75% to 98% and 37.3% to 96%, respectively. The internal reliability (α) of the translated version of the PDQ ranged 0.81-0.86. Conclusions. All the translated instruments reviewed showed good internal consistency of the items, high sensitivity and Positive predictive value (PPV) but not to a suitable level compared with the original version. Therefore, these screening tools are suggested to be used in conjunction with the clinical testing for appropriate diagnosis of patients with neuropathic pain quality.